2014 11th European Radar Conference 2014
DOI: 10.1109/eurad.2014.6991277
|View full text |Cite
|
Sign up to set email alerts
|

A wideband variable width microstrip grid array antenna

Abstract: A wideband planar microstrip grid array antenna is presented. The antenna is realized on a standard Rogers RO3003 substrate. It is fed using two centrally located microstrip vias through a ground aperture. Measured results show a 12% S11 <-10 dB bandwidth and a maximum gain of 17 dBi. Using a variable microstrip line width, a side-lobe suppression of at least -12 dB between 77-85 GHz is measured. The antenna can be used in short and medium range operation for automotive radar.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 11 publications
0
13
0
Order By: Relevance
“…A wideband impedance match of 15% (73. 4 • in the negative Theta direction is however observed in the E-Plane over the operating frequency range. This can be attributed to a slightly asymmetric electric field on the radiating edges of the patch due to the asymmetric ground plane on the PCB top layer below the patch.…”
Section: A) Element Designmentioning
confidence: 91%
See 4 more Smart Citations
“…A wideband impedance match of 15% (73. 4 • in the negative Theta direction is however observed in the E-Plane over the operating frequency range. This can be attributed to a slightly asymmetric electric field on the radiating edges of the patch due to the asymmetric ground plane on the PCB top layer below the patch.…”
Section: A) Element Designmentioning
confidence: 91%
“…As examples, antenna concepts investigated by the authors, as well as other designs reported in literature are used. For multilayer PCB based antennas, the designs from the authors include coaxial fed variable width grid array antenna [4] and SIW slot fed grid array antenna [6] As examples of other designs reported in literature, multilayer grid array antennas reported in [12] for 79 GHz operation and [13] for 60 GHz operation are used. For the hybrid approach, the aperture coupled stacked patch antenna presented in this work and the stacked grid antenna [7] are used as examples.…”
Section: Comparison Of Multilayer Antenna Conceptsmentioning
confidence: 99%
See 3 more Smart Citations